Management Implemented of Stimulation, Detection, and Early Intervention of Growth Toddler At Municipality Jambi; A Qualitative Study - Ena Sari, Rumita; Evy Wisudariani; Esra Lasmarida; Oka Lesmana; Muhammad Syukri (PT Inovasi Pratama Internasional, 2022)
The coverage of Toddler Stimulation Detection and Early Developmental Intervention (SDIDTK) at the Talang Banjar Health Center in Jambi City in 2020 was still far from the target set by the Jambi City Health Office and was the lowest coverage in Jambi City. However, scope of program implementation reached 51%. This study aim to evaluate the management implementation of the Stimulation of Detection and Early Intervention for Toddler Growth and Development (SDIDTK) at the Talang Banjar Health Center. This research was a qualitative study. Data collected from juni-august 2022, by in-depth interviews, observation and document review. In-depth interviews were conducted with 8 informants consisting of public health center employees and mothers with toddlers. In the understanding input component of Permenkes number 66 of 2016 was still lacking, there were staff program who have never received training, the number of available facilities and infrastructure was uncompleted. The components of the process of planning, organizing, workshops, supervision and evaluation, recording and reporting have been going well. Health services running by the program was unoptimal. Coverage has not been achieved because the implementation of SDIDTK for toddlers at the Talang Banjar Health Center has not been optimal. Keywords: Stimulation, Early Detection, Toddler, Public Health Center